A la 1:05 : manual de proceso (2017)
"The principal objetive of this project is to generate an animated story using insights found through a investigation about the "9 de abril". The story is based in my own perspective and conclusions about the causes and consequences of the "9 de abril". In the development of the project, are highlighted the insights that were found in the investigation which were important to realize the story."--Tomado del Formato de Documento de Grado.